Notas sobre a experiência e o saber de experiência - Jorge Bondía Larrosa (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2002)
The text proposes to think education taking the pair experience/sense as its starting point, in opposition to that way of thinking education as a relation between science and technology or between theory and practice. To this end, it explores the meaning of the words experience and sense. With respect to the first, it criticises the excess of information and the obligation of having an opinion, postures which are at the base of significant learning. It also criticises the excess of work which does not allow experience and the very relation work/experience. With relation to sense, this is explored on the basis of the subject of the experience, defined not by his/her activity but by the readiness to be transformed by experience a human passageway, submitted to a logic of passion. It affirms that the knowledge of experience is acquired in the relationship between knowledge and human, singular concrete life.